POTENSI ENDAPAN EMAS SEKUNDER DAERAH MALINAU, KALIMANTAN TIMUR - Hardiyono, Adi (Bulletin of Scientific Contribution, 2014)
The purpose study to recognize and interprete resources of gold deposit in Long Agung, Malinau District, East Kalimantan Province. The field work also to interprete system of gold deposit in research area.